2010
DOI: 10.3390/medicina46020013
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining age-related macular degeneration: a current view

Abstract: Age-related macular degeneration affects the macula and is the leading cause of significant and irreversible central visual loss. It is the most common cause of visual loss in people older than 60 years. The pathogenesis of age-related macular degeneration is complex and not completely understood. It is thought that age-related macular degeneration has a multifactorial etiology, the development of which may be caused by interrelation of environmental and genetic factors and body characteristics. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…CNV is a complex pathogenic process where new blood vessels are generated beneath the retina from pre-existing choriocapillaries (8 -10). Several risk factors have been reported to be associated with CNV formation (11)(12)(13)(14)(15). Studies reported in the literature support a key role for the complement system in the development of CNV (16 -21).…”
mentioning
confidence: 96%
“…CNV is a complex pathogenic process where new blood vessels are generated beneath the retina from pre-existing choriocapillaries (8 -10). Several risk factors have been reported to be associated with CNV formation (11)(12)(13)(14)(15). Studies reported in the literature support a key role for the complement system in the development of CNV (16 -21).…”
mentioning
confidence: 96%
“…3 Drusen may contribute to disease advancement through oxidative stress thought to be inherent to AMD as well as in augmenting the photoreceptor loss, 4 choriocapillaris atrophy, and RPE changes associated with normal aging. 5 While oxidative stress itself, resulting from light energy and oxygen derived free radicals, as well as cigarette smoking 6 , is generally viewed as an environmental risk factor, a genetic predisposition to AMD is also suggested by pedigree analysis. Specifically, family members of affected individuals have demonstrated an increased risk for the disease 7-9 with a concordance rate of 100% among monozygotic twins even noted in one study.…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex disease affecting the macula, a central part of the retina, leading to the irreversible impairment of central vision (Ding et al 2009). The frequency of AMD among adults aged more than 75 years exceeds 30% and is expected to increase due to an increasing life expectancy (Liutkeviciene et al 2010). The early stage of AMD is characterized by druzen formation-a white-yellow deposits in Bruch's membrane under the retinal pigment epithelial (RPE) layer and photoreceptor cells.…”
mentioning
confidence: 99%